INDONESIAN GOVERNMENT EFFORTS TO TEACH VIETNAM IN EXPORTS OF PEPPER IN THE INTERNATIONAL MARKET - Arzila "; Indra Pahlawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted to explain the Indonesian government's efforts to compete with Vietnam in pepper exports on the international market. The low volume of Indonesian pepper production has caused the position of Indonesia which was once the main producer of the world pepper vanished. Along with that, the modern plantation technology and systems used by Vietnam have caused the level of production to increase and has become the world's leading producer of pepper.This research uses the perspective of liberalism with the level of analysis of the nation state, the theory of competitive advantage and the concept of the global value chain. The method used in this study is descriptive-qualitative method that uses secondary data such as books, journals, and several official sites.The results of this study explain some of the efforts that have been made by the Indonesian government to compete with Vietnam pepper exports by improving the domestic pepper plantation system, which is carried out through the Revitalization, Rehabilitation, Intensification and Geographical Indication program. Improve the quality of cooperation with world pepper commodity consumer countries.Keywords: Pepper, Productivity, Competitiveness, Government Efforts